2022
DOI: 10.1002/smtd.202201048
|View full text |Cite
|
Sign up to set email alerts
|

Spin Selectivity in Chiral Hybrid Cobalt Halide Films with Ultrasmooth Surface

Abstract: Introducing chirality into low‐dimensional hybrid organic–inorganic halides (HOIHs) creates brand‐new opportunities for HOIHs in spintronics and spin‐related optoelectronics owing to chirality‐induced spin selectivity (CISS). However, preparing smooth films of low‐dimensional HOIHs with small roughness is still a great challenge due to the hybrid and complex crystal structure, which severely inhibits their applications in spintronic devices. Exploring new lead‐free chiral HOIHs with both efficient spin selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Experiments show that heterogeneity or structural disorder can decrease the CISS response, or even result in a null response, as shown in ref 23, and must be considered when interpreting experiments. Indeed, some of the largest reported spin polarizations are for comparatively rigid well-defined constructs not susceptible to the same types of disorder found in organic molecule self-assemblies, e.g., metal−organic frameworks (>99%), 204 bulk crystals (>70%), 205 metal halides (>90%), 170,175 and perovskites (>90%). 168,172,173 Further evidence corroborating this idea is shown for metal oxides in which films fabricated through electrodeposition techniques, possessing ill-defined crystallinity, exhibit worse polarizations (ca.…”
Section: Organization Effects On Cissmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments show that heterogeneity or structural disorder can decrease the CISS response, or even result in a null response, as shown in ref 23, and must be considered when interpreting experiments. Indeed, some of the largest reported spin polarizations are for comparatively rigid well-defined constructs not susceptible to the same types of disorder found in organic molecule self-assemblies, e.g., metal−organic frameworks (>99%), 204 bulk crystals (>70%), 205 metal halides (>90%), 170,175 and perovskites (>90%). 168,172,173 Further evidence corroborating this idea is shown for metal oxides in which films fabricated through electrodeposition techniques, possessing ill-defined crystallinity, exhibit worse polarizations (ca.…”
Section: Organization Effects On Cissmentioning
confidence: 99%
“…Similar findings have since been reported in hybrid organic–inorganic perovskites and metal halides with other compositions as well (see Table ). In related work, researchers have incorporated achiral additives into the chiral matrix in order to improve the film crystallinity, yet retain their spin-filtering power. , For instance, Lee et al showed that the addition of urea to (R-/S-MBA) 2 PbI 4 perovskites causes structural changes to the perovskite host, which can enhance the chiroptical response and ensuing spin polarization measured by mc-AFM . The spin-filtered currents in these materials can persist over thicknesses of hundreds of nanometers, and it is hypothesized to arise from multiple tunneling processes through the chiral organic molecules occupying the space between the layered octahedral perovskite sheets …”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 99%
“…In 2022, chiral metal halide crystals of (R,S-NEA) 2 CoCl 4 were successfully prepared, in which the stable CH-p interaction enables strong film forming ability. 171 Fig. 20 I-V curves of (a) (R-MBA) 2 SnI 4 and (b) (S-MBA) 2 SnI 4 films obtained by magnetic conductive probe AFM at room temperature.…”
Section: Spin Selective Electron Transfermentioning
confidence: 99%
“…In 2022, chiral metal halide crystals of ( R , S -NEA) 2 CoCl 4 were successfully prepared, in which the stable CH–π interaction enables strong film forming ability. 171 The CISS efficiency is up to 90%. By adding a tiny amount of Alq3 to NEA, an ultrasmooth film with a roughness of 0.3 nm can be obtained.…”
Section: Chiral Properties Of Hybrid Organic Inorganic Perovskitesmentioning
confidence: 99%
“…[1][2][3][4] Alkali-metal batteries are well suited for such energy storage systems because of their high energy density. [5][6][7][8] Among battery metal anodes (e.g., alkali metals Li, Na, and K, or others, such as Ca, Mg, Zn, Al, etc. ), the potassium-metal anodes (PMAs) are the most competitive due to potassium's low cost and low redox potential (−2.93 V vs standard hydrogen electrode).…”
Section: Introductionmentioning
confidence: 99%